2011
DOI: 10.1016/s0034-7094(11)70011-3
|View full text |Cite
|
Sign up to set email alerts
|

Caudal Epidural Anesthesia: An Anesthetic Technique Exclusive for Pediatric Use? Is it Possible to Use it in Adults? What is the Role of the Ultrasound in this Context?

Abstract: Despite its limitations, the ultrasound can be a useful tool to position the needle in the caudal space. It allows prompt identification of the sacral anatomy and real-time visualization of the injection. Considering it is portable, non-invasive, and free of radiation exposure, it is an attractive technique in the operating room especially in difficult cases. However, since its use in neuroaxis anesthesia is very primitive, more studies are necessary to make it a routine technique in anesthetic practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
0
21
0
2
Order By: Relevance
“…A lower-frequency transducer (2)(3)(4)(5) www.ajpmr.com was required in patients with moderate obesity for adequate needle penetration. Chen et al^° reported a 100% success rate in needle placement using a highfrequency transducer (5)(6)(7)(8)(9)(10)(11)(12) to identify the sacral hiatus during US-guided ESI procedures in 70 patients with lumbosacral neuritis. US provides more accurate anatomic information on the site of injection.…”
Section: Discussionmentioning
confidence: 99%
“…A lower-frequency transducer (2)(3)(4)(5) www.ajpmr.com was required in patients with moderate obesity for adequate needle penetration. Chen et al^° reported a 100% success rate in needle placement using a highfrequency transducer (5)(6)(7)(8)(9)(10)(11)(12) to identify the sacral hiatus during US-guided ESI procedures in 70 patients with lumbosacral neuritis. US provides more accurate anatomic information on the site of injection.…”
Section: Discussionmentioning
confidence: 99%
“…Caudal epidural blockade procures successful results in acute pain (in pediatric and adult inguinal and pelvic operations) as well as in chronic pain conditions (particularly in low back pain, pelvic pain, etc.) (13). For many years, caudal blockade had been administered utilizing the landmark technique.…”
Section: █ Materials and Methodsmentioning
confidence: 99%
“…Additionally, a feasibility study of ultrasoundguided epidural steroid injection was done that showed successful placement in 28/29 attempts [43]. Additional studies have utilized ultrasound as an adjunct for measurement prior to epidural injections [44,45].…”
Section: Pain Medicinementioning
confidence: 99%